Rebuilding Jewish Communities after the Holocaust: The American Jewish Joint Distribution Committee’s Relief Programme in Postwar Greece - Tzafleris, Nikos (Historein, 2019)
In the postwar chaos of the Greek Civil War, the Greek state was practically absent in the effort to rebuild the country’s Jewish communities and provide for their particular, post-Holocaust needs. The American Jewish Joint Distribution Committee came to fill this gap. The JDC organised and handled the assistance from American Jews to their coreligionists in Greece, both at the level of distributing humanitarian aid and of reconstituting community life. The JDC played a significant role in reshaping the communal life of postwar Greek Jewry along American lines. This article is mostly focused on the immediate postwar years, when JDC officials sought to establish a network to help Greek Jews cover their most immediate and elementary needs.